Chemical composition of the essential oil of Acorus macrospadiceus (Yam.) F. N. Wei & Y. K. Li from Vietnam - Thai, Tran Huy (Academia Journal of Biology, 2012)
Acorus macrospadiceus (Yam.) F. N. Wei & Y. K. Li (Acoraceae) is a rare plant which distributes in some provinces of Vietnam such as Phu Tho, Thai Nguyen, Vinh Phuc and Bac Giang. This species is listed as endangered in the Red Data Book of Vietnam (1996, 2007). Up to now, there has been no research on Acorus macrospadiceus in Vietnam. The essential oil yielded were 0.2% from air-dried material. GC/MS analysis of the oil resulted in the identification of 31 constituents. The major constituents found in the oil were cis asaron (45.14%), trans asaron (15.49%), b-caryophyllen (12.08%) and neronidol (6.70%).